Towards the poetic paths of Jean-Marie Kerwich in L’évangile du gitan - Boutant, Aurélie (2021)
This paper examines the modes of expression of the gypsy poet Jean-Marie Kerwich in order to unveil his subversive reconceptualization of poetry in a journey space of existential and spiritual resistance. By carrying out a microanalysis of his poems, it highlights the poetic paths created by the poet, inspired by the gypsy-Christian hybrid of his life. Correlatively, it examines the way in which Kerwich incorporates and transforms the disparaging tropes generally deployed in Orientalist cultural productions. He turns them into resources of subversion, critique and vindication in order to open the perspectives of reflection on the various forms of oppression, marginalization and instrumentalization existing in contemporary world.